Protection of Working Time, Rest Time and Welfare for Remote Working Workers in Online Travel Agent Companies - Eka Saputra; Muhammad Ikhwan Al Ghifari; Humairoh Tazkiyatun Nisa (Green Publisher Indonesia, 2025)
The remote working system is a new system choice in the industrial world, the presence of startups or startups is an option used to support productivity during Covid-19 which limits human space to work. Some business fields can implement a remote working system, one of which is an online travel agent company, the selection of this type of business according to research based on research is activities that almost all of its activities can implement a remote working system, researchers conducted research at PT Global Tiket Network by discussing 2 (two) issues, namely the protection of workers in terms of working time rest time and protection of the welfare of workers who apply the remote working system. This research was conducted using a qualitative research method with primary data collection by direct interview to the company. The regulation of the remote working system at PT Global Tiket Network is better regulated than the provisions in the laws and regulations and Company Regulations by implementing a remote working system, namely with 3 (three) working days in the office and 2 (two) working days outside the office and related to welfare, workers at PT Global Tiket Network are satisfied with the wages and welfare facilities received and this has been included in company regulations so that this guarantees workers to work optimally or productively and safely.